Efektivitas Komunikasi Organisasi Melalui Penerapan Sistem Administrasi Persuratan Terintegrasi di Universitas Lampung - Penda Wardani; Tina Kartika (Inter Komunika, 2020)
Communication is needed by humans in individual and organizational activities. Communication in an organization follows the development of the virtual era. Along with that, the needs of institutions have also changed, including the University of Lampung (Unila). The development of this technology used by University of Lampung in overcoming the problems of correspondence administration, such as the administration of correspondence documents that are vulnerable to being lost and the difficulty of knowing the administrative process. Therefore, the University of Lampung established a website-based integrated mail administration system. The correspondence administration system (SAP) is a system that accommodates correspondence administration in the University of Lampung environment in controlling the process of correspondence management, decision letters, and circular regulations of the chancellor. To optimize the application of SAP requires effectiveness of organizational communication. The purpose of this study was to describe the effectiveness of organizational communication through the application of integrated mailing administration systems at University of Lampung in terms of accountable factors, targets, security, fair, and transparent. This research was a quantitative study conducted at the University of Lampung and involved 171 respondents as sample. Based on the results, it was found that the categorical accountable factors were quite effective, the target factors categorized as quite effective, the security factors categorized as quite effective, the fair/non-discriminatory factors categorized as quite effective, and the transparent factors categorized as quite effective in applying SAP. It was concluded that organizational communication in the application of integrated mail administration systems at the University of Lampung had been running quite effectively in terms of accountable factors, targets, security, fair, and transparent.